Image Photograph - Lafia, Marc, 1955-; Coffeen, Daniel (Book collections on Project MUSE., 2020)
Image Photograph is a co-production of punctum books and the Center for Transformative Media, Parsons The New School of Design. Lafia is redefining what it means to be a photographer in an age when everyone is living on both sides of the megapixel equation. These images challenge the boundaries between public and private space, as well as personal and universal truth. ~ Douglas Rushkoff Image-photograph is the impressive tour-de-force of a mind that is equally at ease in thinking through images and in photographing through words. For that alone, this is a must-read. But he does not stop there. Like the old gold-seeker of the past, Marc Lafia excavates the world of contemporary image-making and within the rubble, the debris of our digital age, he points to the only gold nugget left for us: the image-photograph. The latter is not just the image that we see, or the image that we construct: it is the image that we are. Nothing more, but also nothing less. ~ Chiara Bottici Marc Lafia's book seeks to map a new territory, to articulate the strange and beautiful new relationships between world, technology, image, and us. ~ Daniel Coffeen We no longer live in the society of the spectacle, passively seeing the world. Now we perform our very own spectacle in a society that demands it at every turn. We've become advertisements of ourselves, our own PR agents, continually putting on a performance and measuring it hour by hour. This is no longer the society of the spectacle but the society of performance. All events have become a pretense to create the image, to orchestrate an image of images that is us. We believe the image confers on us a kind of immortality: just as the artist believes her works collected by a major museum will do the same, we believe the network will forever host the archive we build everyday. The image that is us lives in the circulation of the network. Though a file, though virtual and malleable, made out of bits and instantly accessible to anyone who wants to find it around the world, this image that lives only lives on screen, as virtual as it might be, is a material fact. In its impression, its reception, its archivability, its remixability, the electronic image is today's photograph. Image Photograph is a book about, and of, this transformation of the image. In three essays -- a foreword by critic and philosopher, Daniel Coffeen; an essay of images and text that explores the varied rhetorics of the image; and a strictly visual essay -- the book presents a traversal through photography to arrive at a new understanding of images, what Lafia calls the image-photograph. As Coffeen states, Lafia takes up the prescribed space of the photograph and, by touring the new conditions of imaging, remaps the very space of photography. Which is to say, Lafia presents and examines imaging across a breadth of moods, tropes, and contexts in order to see and engage this new technology of image-seeing and image-making -- this image-photograph -- as it exists today in our age of electronic inscription and networked culture. At once artist book and critical theory, Image Photograph takes its direction from Walter Benjamin's Arcades, John Berger's Ways of Seeing and, more recently, Hito Steyerl's The Wretched of the Screen. Throughout it, Lafia not only writes about the image but constructs images -- and, finally, performs this new space of the image-photograph.